2019
DOI: 10.1093/mnras/stz2298
|View full text |Cite
|
Sign up to set email alerts
|

EZOA – a catalogue of EBHIS H i-detected galaxies in the northern Zone of Avoidance

Abstract: We present a catalogue of galaxies in the northern Zone of Avoidance (ZoA), extracted from the shallow version of the blind H i survey with the Effelsberg 100 m radio telescope, EBHIS, that has a sensitivity of 23 mJy beam −1 at 10.24 km s −1 velocity resolution. The catalogue comprises 170 detections in the region δ ≥ −5 • and |b| < 6 • . About a third of the detections (N = 67) have not been previously recorded in H i. While 29 detections have no discernible counterpart at any wavelength other than H i, 48 d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
(95 reference statements)
0
7
0
Order By: Relevance
“…Data acquisition with a high time resolution of 0.5 s (Flöer and Winkel 2012) enabled flagging of timevariable RFI. While the compilation of the full extragalactic catalogue is awaiting completion of the final survey scans (Flöer et al 2014), a catalogue from the shallow survey of the northern Zone of Avoidance (δ > −5 • , |b| ≤ 6 • ) is already available by Schröder et al (2019).…”
Section: Effelsberg Hi Surveysmentioning
confidence: 99%
“…Data acquisition with a high time resolution of 0.5 s (Flöer and Winkel 2012) enabled flagging of timevariable RFI. While the compilation of the full extragalactic catalogue is awaiting completion of the final survey scans (Flöer et al 2014), a catalogue from the shallow survey of the northern Zone of Avoidance (δ > −5 • , |b| ≤ 6 • ) is already available by Schröder et al (2019).…”
Section: Effelsberg Hi Surveysmentioning
confidence: 99%
“…Data acquisition with a high time resolution of 0.5 s (Flöer & Winkel 2012) enabled flagging of time-variable RFI. While the compilation of the full extragalactic catalogue is awaiting completion of the final survey scans (Flöer, Winkel & Kerp 2014), a catalogue from the shallow survey of the northern Zone of Avoidance (δ > −5 • , |b| ≤ 6 • ) is already available by Schröder et al (2019).…”
Section: Effelsberg Hi Surveysmentioning
confidence: 99%

WALLABY -- An SKA Pathfinder HI Survey

Koribalski,
Staveley-Smith,
Westmeier
et al. 2020
Preprint
“…They then compared their results with a dozen known galaxy clusters, including the presence of the more distant Vela super-cluster (Kraan-Korteweg et al 2017), and found a remarkable agreement. Finally, Schröder et al (2019b) presented detections of 170 galaxies in the northern ZoA at |𝑏| < 6 • , of which a third of these had no previous HI observations.…”
Section: Introductionmentioning
confidence: 98%